Pemberian Stretching Dan Core Stability Dengan Kondisi Nyeri Punggung Bawah Miogenik : Literature Review - , Zulfikar H. Wada; Robiatun Amaliyah, Ranti; Inatonia Inatonia (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Objective : This study aims to determine the Provision of Stretching and Core Stability with Myogenic Low Back Pain Conditions. Research Method : This research method uses a Literature Review approach. The literature was obtained from 2 databases, namely: Pubmed and Google Scholar. The research sample was patients with low back pain, provision of Stretching and Core Stability, male and female gender, year of publication was the last 10 years (2014-2024), the variables measured were the Visual Analog Scale (VAS) and Oswestry Disability Index (ODI). Exclusion criteria were patients without low back pain, vertebral fractures, in addition to using stretching and core stability interventions. Results : Based on the 20 literatures that have been collected, the results of the most dominant number of literatures in 2020 were 5 literatures, study designs with an average of RCT (Randomized Control Trial) of 15 literatures, besides that there were experimental with 3 literatures then A quasi-dominated control trial with 1 literature and the This multicenter, non-randomized, pilot clinical trial with 1 literature. Conclusion : All journals analyzed showed that Stretching and Core Stability were significantly effective in reducing pain and increasing functional activity in patients with low back pain. This decrease in pain and increase in functional activity were directly seen from the patient's ability to carry out daily activities.